The Continuity of Palm Sugar Production: A Literature Review - Simamora, Liska; Zebua, Damara Dinda Nirmalasari; Handoko, Yoga Aji; Widyawati, Nugraheni (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2021)
The demand for palm sugar is increasing since people prefer natural ingredients. Natural and organic food ingredients have the reputation of being healthier and safer than synthetic ingredients. This study will discuss one particular ingredient namely palm sugar which is known as a natural sweetener. Developed countries have started to import palm sugar as a natural sweetener from developing countries. The production of palm sugar in developing countries has an important benefit in the craftsman household economy. However, current production of palm sugar does not meet the increasing demand, which is caused mainly by the lack of farmers, palm sugar craftsmen’s inadequate knowledge of palm sugar production, and poor incorporation of technology both in the cultivation of palm tree and the production process of palm sugar. This literature review study aims to understand the continuity of palm sugar production within the following framework which consists of four steps: (1) identifying current situation, (2) identifying the problems, (3) presenting the resolution, (4) proposing programs and strategies. Based on this framework a few programs and strategies are generated to maintain the continuity of palm sugar production, they are: (1) Palm trees domestication, (2) research and development center for Indonesian palm sugar, and (3) ensuring a good collaboration among the stake holders involved.